Bankruptcy linked to early mortality in patients with cancer. (5th May 2016) - Barton, Mary Kay
Key Points: Financial distress is common in patients with cancer. Filing for bankruptcy is a risk factor for early mortality in patients with cancer. Policy interventions are needed to protect patients, and practitioners need to discuss the financial aspects of care with their patients.